The ‘Prioritizing Safety for Sex Workers Policy’: A sex worker rights and anti-trafficking initiative - Lutnick, Dr Alexandra (Anti-Trafficking Review, 2019)
This article presents a case study of how sex worker and anti-trafficking organisations and activists in San Francisco, California, worked together to develop and pass the ‘Prioritizing Safety for Sex Workers Policy’. This policy, as enacted by the San Francisco District Attorney’s Office and the San Francisco Police Department, creates a legal environment where people can come forward and report to law enforcement when they are a victim of or witness to an array of violent crimes while engaged in sex work, and not be arrested or prosecuted for their involvement in that criminalised behaviour or for any misdemeanour drug offences. The article details how the groups came together and the challenges they faced while developing the policy. The work was fuelled by the recognition that no one wants people in the sex industry to experience violence. That is true whether selling sex is their choice, influenced by their life circumstances, or something they are being forced or coerced to do. The Prioritizing Safety for Sex Workers Policy is a unique example of the way in which sex workers, people who have experienced trafficking, service providers, activists, women’s rights policymakers, the police department, and the District Attorney’s office came together around a common goal.